Agrarian Conflict Cultivation Rights PT. Pagilaran With Farmers In Batang District - Silvia Cahyadi; Anisa Puspitasari; Mishael Joshua (Universitas Trunodjoyo Madura, 2023)
This study aims to identify the causes of conflict between PT. Pagilaran and the community in Batang Regency over land owned by PT. Pagilaran comes from the concession with revealing theories that support the causes of conflict and studies how the dispute is resolved. This research is normative juridical research with a descriptive-analytical approach. The research results obtained: First, the cause of the emergence of Cultivation Right disputes is the claims from farmers that they once controlled part of the Cultivation Right land, the absence of compensation at the time of land acquisition, and the negative view of the community towards PT. Pagilaran and some parties facilitate claims efforts, as well as repressive actions from the company through security forces. Second, efforts to resolve the dispute are carried out both through channels outside the court, through efforts to seek support from policy-making institutions, and through re-data collection of biological data on PT. Pagilaran looked for opportunities to strengthen the position of farmers who once controlled the land and settlement through the courts in the form of legal action for the perpetrators of marking, plotting, and damage to land and plants in the Cultivation Rights area but did not resolve the core issues of the dispute. This study suggests that rural conflict resolution requires a holistic approach by paying attention to regulatory, human rights, contractual, and environmental aspects of resolving conflicts.